Isolation, Identification, and Antibacterial Mechanisms of Bacillus amyloliquefaciens QSB-6 and Its Effect on Plant Roots - Duan, Yanan; Chen, Ran; Zhang, Rong; Jiang, Weitao; Chen, Xuesen; Yin, Chengmiao; Mao, Zhiquan (Frontiers in Microbiology, 2021)
Apple replant disease (ARD) is a common problem in major apple planting areas, and biological factors play a leading role in its etiology. Here, we isolated the bacterial strain QSB-6 from the rhizosphere soil of healthy apple trees in a replanted orchard using the serial dilution method. Strain QSB-6 was provisionally identified as Bacillus amyloliquefaciens based on its morphology, physiological and biochemical characteristics, carbon source utilization, and chemical sensitivity. Maximum likelihood analysis based on four gene sequences (16S rDNA, gyrA, gyrB, and rpoB) from QSB-6 and other strains indicated that it had 100% homology with B. amyloliquefaciens, thereby confirming its identification. Flat standoff tests showed that strain QSB-6 had a strong inhibitory effect on Fusarium proliferatum, Fusarium solani, Fusarium verticillioides, Fusarium oxysporum, Alternaria alternata, Aspergillus flavus, Phoma sp., Valsa mali, Rhizoctonia solani, Penicillium brasilianum, and Albifimbria verrucaria, and it had broad-spectrum antibacterial characteristics. Extracellular metabolites from strain QSB-6 showed a strong inhibitory effect on Fusarium hyphal growth and spore germination, causing irregular swelling, atrophy, rupture, and cytoplasmic leakage of fungal hyphae. Analysis of its metabolites showed that 1,2-benzenedicarboxylic acid and benzeneacetic acid, 3-hydroxy-, methyl ester had good inhibitory effects on Fusarium, and increased the length of primary roots and the number of lateral roots of Arabidopsis thaliana plantlet. Pot experiments demonstrated that a QSB-6 bacterial fertilizer treatment (T2) significantly improved the growth of Malus hupehensis Rehd. seedlings. It increased root length, surface area, tips, and forks, respiration rate, protective enzyme activities, and the number of soil bacteria while reducing the number of soil fungi. Fermentation broth from strain QSB-6 effectively prevented root damage from Fusarium. T-RFLP and qPCR assays showed that the T2 treatment significantly reduced the abundance of Fusarium in the soil and altered the soil fungal community structure. In summary, Bacillus amyloliquefaciens QSB-6 has a good inhibitory effect on Fusarium in the soil and can significantly promote plant root growth. It has great potential as a biological control agent against ARD.